Public Perception of MUI Fatwa Number 1 of 2021 concerning Giving Money to Beggars in Makassar City, South Sulawesi: Perspectives on Positive Law and Islamic Law - M, Ramadhani. (MUI Sulawesi Selatan, 2022)
This study aims to analyze public perceptions of MUI Fatwa Number 1 of 2021 which regulates giving money to beggars from the point of view of positive law and Islamic law. In social and religious contexts, the issue of giving money to beggars has become a complex debate with significant social and economic implications. This study uses a comparative legal approach between positive law and Islamic law to understand the prevailing legal view. The research method used is a qualitative approach by collecting data through in-depth interviews and analysis of documents related to fatwas and related regulations. The study respondents consisted of various walks of life, including academics, legal practitioners, and religious leaders. The results of the analysis show variations in views in society regarding the effectiveness and compliance with MUI Fatwa Number 1 of 2021 on positive legal considerations, while other views refer to interpretations of Islamic law and social values. From a positive legal perspective, the fatwa reflects an attempt to regulate the practice of giving money to beggars in order to address potential exploitation and abuse. However, from the perspective of Islamic law, there are nuances of humanity and solidarity that must be taken into account in the context of giving alms. This study also illustrates how people's views can be influenced by cultural factors, social environment, and religious understanding. The results of the study show that MUI fatwa Number 1 of 2021 concerning Exploitation and begging activities on the streets and public spaces turns out that there are still many who do not know about the existence of the fatwa, and do not agree with the existence of the fatwa. The existence of a haram fatwa regarding giving money to beggars is done to stop human exploitation, the fatwa is the result of a study. The issuance of MUI Fatwa number 1 of 2021 concerning exploitation and begging activities on the streets and public spaces to support Regional Regulation Number 2 of 2008 concerning the development of street and sprawl children so that the government prioritizes making programs that further suppress high social problems. While in Islamic law, MUI fatwas do not contradict Islamic law. The fatwa does not necessarily prohibit Muslims from giving or receiving alms in its entirety or universally. Only in certain places and through other means. The implication of this research is that in upholding law and justice, law enforcement should conduct socialization related to legal problems that often occur, so that ordinary people can understand the legal consequences they cause in public life.